Microbial competition for nitrogen and carbon is as intense in the subsoil as in the topsoil. (February 2018) - Jones, D.L.; Magthab, E.A.; Gleeson, D.B.; Hill, P.W.; Sánchez-Rodríguez, A.R.; Roberts, P.; Ge, T.; Murphy, D.V.
Abstract: Most studies on plant nutrition tend to focus on the topsoil (plough layer) and frequently neglect subsoil processes. However, cereal roots can potentially acquire nutrients including organic and inorganic nitrogen (N) from deep in the soil profile. Greater knowledge on the interaction of plants and microbes in subsoil environments is required to evaluate whether deep rooting traits in cereals will achieve greater nutrient use efficiency and greater soil carbon (C) storage in cropping systems. This study aimed to evaluate the relationship between root distribution, organic and inorganic N availability and potential N supply at the critical growth period during the wheat cropping cycle in a sand textured Eutric Cambisol. Our results provide evidence of significant microbial capacity in the subsoil. The rate of plant residue turnover and the mineralization of organic C and N substrates (glucose, amino acids, peptides, protein) declined slightly with increasing soil depth; however, these rates were not correlated with basal soil respiration, microbial biomass or community structure. This suggests that the microbial population in subsoil is more C limited but that its activity can be readily stimulated upon C substrate addition. A significant potential for organic and inorganic N turnover was also demonstrated at depth with a similar abundance of ammonifiers and ammonia oxidizing bacteria (AOB) and archaea (AOA) throughout the soil profile. Again, N mineralization in subsoils appears to be substrate limited. Root density declined rapidly down the soil profile with few roots present past 50 cm; suggesting that this is the major factor limiting C recharge of soil organic matter and microbial activity in subsoils. Greater root proliferation at depth could allow greater capture of water and the recapture of N lost by leaching; however, our results suggest that plant-microbial competition for C and N is as intense in the subsoil as in the topsoil. We conclude that while deeper rooting may improve nutrient and water use efficiency it may not lead to much greater C sequestration in subsoils, at least in the short term. Highlights: Microbial community composition changes with soil depth. Subsoil microbial activity increases rapidly on DOC and DON substrate addition. Microbial activity in subsoils is not nitrogen limited. Nitrogen mineralization in subsoils is substrate limited. Greater root proliferation at depth may not lead to greater C sequestration.